Pengaruh Penempatan Kerja, Kompetensi, dan Pengembangan Karir Terhadap Kinerja Pegawai ASN Pada Kantor Dinas Perhubungan Kabupaten Mamuju - Zulkarnaen, Rofi; Aqil, Muhammad; Rasyid, Rohsita Amalyah; Dahri, Nur Wahyunianti (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
This research aims to determine the influence of job placement, competency and career development on employee performance at the Mamuju Regency Transportation Service Office. The research method used is a quantitative method with data taken using a questionnaire. The population in this study were all employees who worked at the Mamuju Regency Transportation Service office. The number of samples calculated was 38 people. The data obtained will be analyzed using validity tests, reliability tests, multiple linear regression, t tests, and simultaneous tests. The results of the T test reveal that partially work placement has a positive and significant effect on employee performance at the Mamuju Regency Transportation Service Office, Competency has a positive and significant effect on employee performance at the Mamuju Regency Transportation Service Office, and career development has a positive and significant effect on employee performance at the Office. Mamuju Regency Transportation Service. The results of the f test show that work placement, competency and career development jointly influence employee performance at the Mamuju Regency Transportation Service Office